2019
DOI: 10.1016/j.schres.2019.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from daily-life stressors in early and chronic psychosis

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 45 publications
3
46
0
Order By: Relevance
“…Notwithstanding, several studies have also reported higher levels of self‐rated paranoia in ARMS as compared to FEP participants, as well as ESE and depressive symptoms (An et al ., 2010), positive self‐schemas (Taylor et al ., 2014), emotional reactivity to stress (Palmier‐Claus, Dunn, & Lewis, 2012) and psychotic experiences (Reininghaus et al ., 2016; van der Steen et al ., 2017). Of note, a recent ESM study that used previously collected data from six ESM studies in samples along the psychosis continuum (NARSAD, MAPS, EUGEI, STRIP1, STRIP2, iTHINK) found that ESM ratings of suspiciousness, tension and negative affect were higher in ARMS individuals than in chronic psychosis patients (Vaessen et al ., 2019). Two major issues could influence this pattern of results.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, several studies have also reported higher levels of self‐rated paranoia in ARMS as compared to FEP participants, as well as ESE and depressive symptoms (An et al ., 2010), positive self‐schemas (Taylor et al ., 2014), emotional reactivity to stress (Palmier‐Claus, Dunn, & Lewis, 2012) and psychotic experiences (Reininghaus et al ., 2016; van der Steen et al ., 2017). Of note, a recent ESM study that used previously collected data from six ESM studies in samples along the psychosis continuum (NARSAD, MAPS, EUGEI, STRIP1, STRIP2, iTHINK) found that ESM ratings of suspiciousness, tension and negative affect were higher in ARMS individuals than in chronic psychosis patients (Vaessen et al ., 2019). Two major issues could influence this pattern of results.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated stress sensitivity is a psychological mechanism that has been widely studied in daily life using the Experience Sampling Method (ESM; Myin-Germeys & van Os, 2007;, 2018Oorschot, Kwapil, Delespaul, & Myin-Germeys, 2009). Stress sensitivity has been conceptualized as increased negative affect and psychotic experiences in response to minor stressors in daily life and has been found in both individuals with an increased familial and psychometric risk for psychosis as well as individuals diagnosed with a psychotic disorder (Collip et al, 2011;Lataster et al, 2009;Myin-Germeys & van Os, 2007;Myin-Germeys, van Os, Schwartz, Stone, & Delespaul, 2001;Palmier-Claus, Dunn, & Lewis, 2012;Reininghaus et al, 2016bReininghaus et al, , 2016cvan der Steen et al, 2017). Also, several models propose that the effects of stress on psychotic experiences are partly mediated through experiences of affective disturbance (Garety et al, 2007;Myin-Germeys & van Os, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For that, a design is needed that allows for the prospective and detailed assessment of the impact of minor perturbations in the flow of daily life on mental states. To our knowledge, only one recent study, by Vaessen and colleagues [18], examined in this way the speed of the affect recovery from daily stressors in groups with various levels of psychopathology. They found that speed of affect recovery was slower in people at early stages of psychosis compared to healthy volunteers and people with already developed psychosis.…”
Section: Introductionmentioning
confidence: 99%
“…These adolescents come from the TWINSSCAN data set which includes baseline time-series data on affect states and daily unpleasant events, combined with baseline and follow-up assessments of (subclinical) psychopathology in a large sample of adolescents. Using a similar approach to measure the concept of "speed of recovery" as Vaessen and colleagues [18], we examined how quickly people recovered in terms of their experienced affect states from small negative events, reflecting minor perturbations, that happened throughout the day (e.g., spilled coffee, traffic jams).…”
Section: Introductionmentioning
confidence: 99%